Effect of the acylation of TEAD4 on its interaction with co‐activators YAP and TAZ. (11th November 2017) - Mesrouze, Yannick; Meyerhofer, Marco; Bokhovchuk, Fedir; Fontana, Patrizia; Zimmermann, Catherine; Martin, Typhaine; Delaunay, Clara; Izaac, Aude; Kallen, Joerg; Schmelzle, Tobias; Erdmann, Dirk; Chène, Patrick
Abstract: The Hippo pathway is deregulated in various cancers, and the discovery of molecules that modulate this pathway may open new therapeutic avenues in oncology. TEA/ATTS domain (TEAD) transcription factors are the most distal elements of the Hippo pathway and their transcriptional activity is regulated by the Yes‐associated protein (YAP). Amongst the various possibilities for targeting this pathway, inhibition of the YAP:TEAD interaction is an attractive strategy. It has been shown recently that TEAD proteins are covalently linked via a conserved cysteine to a fatty acid molecule (palmitate) that binds to a deep hydrophobic cavity present in these proteins. This acylation of TEAD seems to be required for efficient binding to YAP, and understanding how it modulates the YAP:TEAD interaction may provide useful information on the regulation of TEAD function. In this report we have studied the effect of TEAD4 acylation on its interaction with YAP and the other co‐activator transcriptional co‐activator with PDZ‐binding motif (TAZ). We show in our biochemical and cellular assays that YAP and TAZ bind in a similar manner to acylated and non‐acylated TEAD4. This indicates that TEAD4 acylation is not a prerequisite for its interaction with YAP or TAZ. However, we observed that TEAD4 acylation significantly enhances its stability, suggesting that it may help this transcription factor to acquire and/or maintain its active conformation. Abstract : PDB Code(s):5OAQ